On Instant Scripture and Proximal Texts: Some Insights into the Sensual Materiality of Texts and their Ritual Roles in the Hebrew Bible and Beyond. Issue 1 (3rd July 2017) - Frevel, Christian
Abstract : The paper discusses the importance of writing in the Hebrew Bible beyond the information storage aspect of script. Writing in the Torah is by no means limited to the textualization of tradition. The visual representation of writing, its materiality and the sensual experience are significant aspects of script and scripture. In four case studies the paper develops various aspects of writing as symbolic representation, performativity and agency of script. The four examples comprising various genres of texts are Deuteronomy 27, Deuteronomy 6, Exodus 28 and Numbers 6. The case studies evince the transformation from writing processes to the symbolic meaning of a scripturalized Torah as well as scripture as medium in various ways.